Targeting Lung Cancer Stem Cells with Antipsychological Drug Thioridazine. (31st July 2016) - Yue, Haiying; Huang, Dongning; Qin, Li; Zheng, Zhiyong; Hua, Li; Wang, Guodong; Huang, Jian; Huang, Haixin
Abstract : Lung cancer stem cells are a subpopulation of cells critical for lung cancer progression, metastasis, and drug resistance. Thioridazine, a classical neurological drug, has been reported with anticancer ability. However, whether thioridazine could inhibit lung cancer stem cells has never been studied. In our current work, we used different dosage of thioridazine to test its effect on lung cancer stem cells sphere formation. The response of lung cancer stem cells to chemotherapy drug with thioridazine treatment was measured. The cell cycle distribution of lung cancer stem cells after thioridazine treatment was detected. The in vivo inhibitory effect of thioridazine was also measured. We found that thioridazine could dramatically inhibit sphere formation of lung cancer stem cells. It sensitized the LCSCs to chemotherapeutic drugs 5-FU and cisplatin. Thioridazine altered the cell cycle distribution of LCSCs and decreased the proportion of G0 phase cells in lung cancer stem cells. Thioridazine inhibited lung cancer stem cells initiated tumors growth in vivo. This study showed that thioridazine could inhibit lung cancer stem cells in vitro and in vivo. It provides a potential drug for lung cancer therapy through targeting lung cancer stem cells.